THE INFLUENCE OF USING PODCAST TOWARD LISTENING COMPREHENSION - Nur Oktaviani; Fenny Thresia (Language and Education Journal, 2021)
Listening is an individual concentration on specific aspects of aural information, build context from passages, and connect what they hear to prior experience. Unfortunately, listening activities are rarely given to students. The problem is formulated as follow: “Is there any significant difference of using video podcast toward listening comprehension of students majoring in Multimedia at the first grade of SMK 4 Metro?”.The research design was quasi-experimental. The students Majoring in Multimedia at first grade SMK 4 Metro as population. To assess the students’ listening comprehension, the researcher used a written test. Based on the result, the significance score of 0.002 was smaller than t table 0.05, which meant that Ha was accepted and there was a significant difference between students who taught by using podcast and those who were not. As a result, podcasts became an enjoyable medium to use in teaching listening skill